HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM SOAL - Iis Siti Aisyah; Galih Dani Septiyan Rahayu (IKIP Siliwangi, 2021)
This study aims to determine the scenario and implementation of learning for fourth grade elementary school students, to find out teacher responses and student responses and to find out the difficulties faced by students during learning using cooperative learning models, greeting techniques and questions. This research uses descriptive qualitative method. The instruments are used through observation, questionnaires, interviews and tests. Learning is related to student achievement, student learning achievement results will increase with a pleasant classroom atmosphere. Creating a pleasant classroom atmosphere is by applying learning models, one of which is the cooperative model of sending greetings and questions. Through the cooperative learning model, the technique of sending greetings and questions, students can practice their ability to make their own questions and answer questions made by their friends, so that students will better understand the material taught by the teacher. Thus, the application of the cooperative learning model of greeting techniques and questions will be able to improve the PPKn learning process in schools to be more effective, because students can actively participate in the learning process and the learning outcomes achieved will be better.